Modulatory effects of auditory cortex projections on superior colliculus auditory responses - Hongli Hu; Fulian Wu; Yi Liang; Xuying Ji (Brain Research Bulletin, 2025)
Background: The superior colliculus (SC) plays a critical role in auditory-related behaviors, receiving descending inputs from the auditory cortex (AC). However, the modulatory effects of AC projections on SC auditory responses remain unclear. This study focuses on elucidating how AC corticofugal projections modulate SC neuronal activity in response to auditory stimuli in mice. Methods: We combined viral tracing, in vitro and in vivo electrophysiology, and optogenetics in mice to investigate the corticofugal modulation of SC neurons by AC projections. Results: Layer 5 (L5) pyramidal neurons in the AC send dense projections to the intermediate and deep layers of the SC. While SC neurons exhibit strong auditory responses to noise, they show weaker frequency selectivity to pure tones compared to SC-projecting neurons in the AC. Optogenetic inhibition of the AC significantly suppressed auditory responses in the SC, reducing firing rates, increasing response thresholds, narrowing frequency bandwidth, decreasing the number of spikes and shifting the best frequency (BF) toward lower frequencies. Conclusions: These findings reveal that AC corticofugal projections regulate auditory responses in SC neurons in mice, potentially modulating auditory-related behaviors.